Cellulolytic activities of the rumen ingesta of goats - Abd Aziz, S. A. B.; AbdRazak, M. F. B. (Malaysian Journal of Science, 1994)
A normal grass-fed goat has rumen pH non-inhibitory for the microbial population, highest ruminal of sugar in the dorsal rumen and volatile fatty acids in the ventral rumen. Endoglucanase activity was 12.9 times higher than exoglucanase activity with maximum activity in the dorsal rumen. The digestion of PONE fibre was better than crystalline cellulose and grass fibre with the latter the least digested. Apart from the swollen cellulose, the digestion of the other forms of cellulose was better in the ventral rumen than the other parts of the rumen. Supplementing grass-fed goat with high carbohydrate and protein but low fibre-diet, increased the concentration of ruminal sugar and volatile fatty acids with maximum concentrations in the ventral rumen. The rumen microbial population increased and was highest in the dorsal rumen. The rumen pH decreased to a level inhibitory for cellulolytic activities. The relative digestibility of the different form of cellulose was the same as in the rumen of the grass fed goat but endoglucanase activity decreasedby 1.8 times. However, apart from the swollen cellulose, the digestion of the other forms of cellulose was better in the dorsal part of the rumen. However, diet supplementing of the grass-fed goat with low carbohydrate, low protein and low fibre diet with low cellulose content decreased the concentration of soluble sugar and volatile fatty acids. It also decreased the number of rumen microorganisms. The pattern was similar to that observed for the grass-fed goats. Swollen cellulose was Ã gain the best digestible form of cellulose but the activity was lower thÃ n that in the grass-fed goat. The digestion of crystalline cellulose was better than PON’Å’ and grass fibre. The digestion of the different forms of cellulose was better in the velfral part of the rumen.